A2.18 Induction and characterisation of the dominant IL-10 producing B cell subset in healthy blood donors and rheumatoid arthritis patients. (24th February 2016) - Bankó, ZS; Pozsgay, J; Tóth, M; Gáti, T; Nagy, G; Rojkovich, B; Sármay, G
Abstract : Background and objectives: The most important feature of B-cells is the production antibodies upon activation; additionally, B-cells produce both pro-inflammatory and anti-inflammatory cytokines in response to certain stimuli. IL-10 producing B10 cells represent a major subset of regulatory B-cells (Bregs). Bregs suppress autoimmune and inflammatory responses by multiple mechanisms. B-cells play crucial role in the development and maintenance of the chronic inflammatory autoimmune disease, Rheumatoid arthritis (RA); however, controversial data are available on B10 population in RA. Our aim was to identify the optimal conditions inducing B10 cells in samples from healthy controls and RA patients; furthermore, to shed light on signalling pathways resulting in the expansion of the B10 subset. Materials and methods: Peripheral blood mononuclear cells (PBMC) were isolated from heparinized blood of healthy donors and RA patients. B cells were purified by magnetic separation, using negative selection. We assessed IL-10 and TNF expressing B-cells after intracellular staining by flow cytometry, and measured the secreted cytokines with multiplex bead array. Phosphorylation of key signalling molecules was monitored by phospho-flow method. Results: The results show that dual stimulation by CpG and CD40L for 48h was optimal for IL-10 induction, which was synergistically boosted by IL-21. We identified CD19 + CD27 + memory B-cells as the major source of B10 cells. IL-21 increased the ratio of BLIMP1 and IL-10 double positive plasmablasts. In RA patients we detected significantly less CD27 + B10 cells as compared to the controls, while addition of IL-21 to the dual stimuli significantly elevated the number of B10 cells both in the CD19 + CD27 + and in the CD19 + CD27 - population. Different combinations of stimuli induced preferentially the secretion of pro-inflammatory cytokines (TNF, IFNγ, IL-17) and the suppressor cytokine, IL-10. We assumed that activation of ERK, p38 and CREB are indispensable to induce IL-10, while STAT3 appears to be a co-activator for IL-10 transcription in human Bregs. Conclusions: CD19 + CD27 + memory B-cells are the major source of human B10 cells, which may expand and differentiate to IL-10 producing plasmablasts in the presence of IL-21. CREB and the co-activator STAT3 are the key transcription factors responsible for the expansion of the B10 population. Support: National Research, Development and Innovation Office (OTKA104846), and ELTE TÁMOP 4.2.1./B-09/1/KMR-2010–0003